Pillar[5]arene-based supramolecular pseudorotaxane polymer material for ultra-sensitive detection of Fe3+ and F−. Issue 18 (19th April 2023) - Zhu, Wen-Bo; Wei, Tai-Bao; Hu, Hao-Bin; Li, Zhi-Jun; Zhang, Yu-Quan; Li, Yan-Chun; Zhang, Liang; Zhang, Xiao-Wei
Abstract : Recent advancements in ultra-sensitive detection, particularly the Aggregation Induced Emission (AIE) materials, have demonstrated a promising detection method due to their low cost, real-time detection, and simplicity of operation. Abstract : Recent advancements in ultra-sensitive detection, particularly the Aggregation Induced Emission (AIE) materials, have demonstrated a promising detection method due to their low cost, real-time detection, and simplicity of operation. Here, coumarin functionalized pillar[5]arene (P5C ) and bis-bromohexyl pillar[5]arene (DP5 ) were successfully combined to create a linear AIE supramolecular pseudorotaxane polymer (PCDP-G ). The use of PCDP-G as a supramolecular AIE polymer material for recyclable ultra-sensitive Fe 3+ and F − detection is an interesting application of the materials. According to measurements, the low detection limits of PCDP-G for Fe 3+ and F − are 4.16 × 10 −10 M and 6.8 × 10 −10 M, respectively. The PCDP-G is also a very effective logic gate and a material for luminous displays.